Elucidating efficacy of biomass derived nanocomposites in water and wastewater treatment - Kirti, Saumaya; Bhandari, Vinay M.; Jena, Jyotsnarani; Bhattacharyya, Arnab S (Journal of environmental management, 2018)
In the present study, two synthesis methods of nanocomposites-one involving a mixture of biomass and the other using chemical modification were investigated to evaluate practical application of green approach in pollution control, specifically for water and wastewater treatment. Newer multifunctional superparamagnetic nanocomposites using biomaterials such as unripened fruit of Cassia fistula (Golden shower) and Aloe vera were developed as an example of green approach while chemical modification was illustrated using n-octanol. Two specific model applications were studied for the developed materials-dye removal (Methyl Blue and Congo Red) and disinfection-demonstrating antimicrobial property. To elucidate the multifunctional character, the texture, morphology and composition of the prepared bionanocomposites were studied. The surface area values were 6.2 and 9.8 m(2)/g for Aloe vera and octanol based nanocomposites while the average pore diameters were 1.79 nm and 5.7 nm respectively, indicating presence of highly developed micropores in the first material having a honeycomb shape and the later showing excellent staircase type formation with larger pores. A very high dye removal to the extent of 100% was obtained that can be attributed largely to the functionalities imparted from Cassia fistula compared to ingredients from Aloe vera and octanol. The nanomaterials could be completely separated with absolute ease by applying simple magnetic field. Also, successful application of the developed materials in disinfection, removal of E. coif, was demonstrated with a very high efficiency of over 95%. The biomass derived nanocomposites exhibit excellent pollutant removal and disinfection properties, even at very low nanoparticle content; octanol based material indicating similar to 5 times lowered cost, while the Aloe vera based bionanocomposites have potential for cost reduction to the extent of 10 times as compared to only magnetite nanoparticles, thereby highlighting techno-economical alternative in water and wastewater treatment.

Exploiting functionalities of biomass in nanocomposite development: application in dye removal and disinfection along with process intensification - Kirti, Saumaya; Bhandari, Vinay M.; Jena, Jyotsnarani; Sorokhaibam, Laxmi Gayatri; Bhattacharyya, Arnab S. (Clean Technologies and Environmental Policy, 2018)
A green synthesis of multifunctional superparamagnetic nanocomposites using the whole unripened fruit of Cassia fistula (Golden shower) with potential for removal of both cationic and anionic dyes and antimicrobial property is reported for the first time in the present work. A natural medium in the form of clarified butter was used to enhance the multifunctional character. The surface morphology, textural characteristics and composition of the prepared nanoparticles and composites were studied to understand the multifunctional nature. The dye removal was investigated for four different dyes, namely methyl blue, Congo red, rhodamine-B and auramine. Iron nanoparticles were largely effective in the removal of acidic dyes, while the magnetic nanocomposites were effective for the removal of both acidic and basic dyes which can be attributed to the functionalities imparted from Cassia fistula and clarified butter. The dye removal behavior can be significantly enhanced (similar to 50%) using process intensification-adsorption coupled with acoustic cavitation, which also indicated a reduced adsorbent loading as compared to the conventional adsorptive dye removal. The nanomaterials were completely separated from dye solution with absolute ease of separation by applying simple magnetic field. Also, the developed materials were useful in disinfection of E. coli with a high efficiency of 90% confirming significant antimicrobial property at lower concentrations.

Hydrodynamic cavitation using vortex diode: an efficient approach for elimination of pathogenic bacteria from water - Jain, Pooja; Bhandari, Vinay M.; Balapure, Kshama; Jena, Jyotsnarani; Ranade, Vivek V.; Killedar, Deepak J. (Journal of Environmental Management, 2019)
The present study successfully demonstrates greener methodology of hydrodynamic cavitation using rotational flows for disinfection of water. Disinfection of two model microbial strains-gram-negative (Escherichia colt) and gram-positive (Staphylococcus aureus) using vortex diode was evaluated. The removal efficacy was quantified for two different cavitation reactors. Practically complete elimination of E. coli was achieved (99%) after 1 h of cavitation at a pressure drop of only 0.5 bar. However, elimination of S. aureus using vortex diode was observed to be lower in comparison to the removal of E. coli and only 60% disinfection could be achieved under similar conditions, which can be subsequently enhanced up to 98% by increasing pressure drop. The results were compared with another cavitating device that employs linear flow for cavitation, orifice. The reactor geometry has significant impact on the disinfection process and orifice was found to require significantly higher pressure drop (10 bar) conditions for disinfection and for eliminating grain-positive bacteria with high efficiency. A plausible mechanism for disinfection was proposed to elucidate the role of cavitation in cell destruction leading to death of cells through the rupture of cell wall, oxidative damage and possible DNA denaturation. Also, a cavitation model using per pass disinfection was developed that can provide meaningful physical description of the disinfection process as against the conventional first order reaction rate model. This study would provide meaningful insight into cavitation process based on hydrodynamic cavitation for the destruction of both gram-negative and gram-positive bacteria from various water sources, including industrial wastewaters.
Keywords: Cavitation; Disinfection; kinetics; pollution; Wastewater treatment